Spectrum of Hematological Malignancies and Peripheral Cytopenias - Jha, A (Journal of Nepal Health Research Council, 2014)
Background: Peripheral cytopenias such as anemia, thrombocytopenia, bicytopenia and pancytopenia are common peripheral blood findings in hematological malignances for which bone marrow evaluation is often required. The study was conducted to identify the spectrum of hematological malignancies in association with peripheral cytopenia. Methods :One year retrospective study was conducted in Tribhuvan University Teaching Hospital. Data of bone marrow examination were retrieved from the archives of the hematology department and analyzed. Results: Total number of hematological malignancies out of 400 cases of bone marrow examination was 86 (21.5%). Median age was 13 years. 48 (55.81 %) were children. Male: female ratio was 1.26:1. Frequency of bicytopenia, pancytopenia, anemia and thrombocytopenia were 34.88%, 23.25%, 23.25% and 9.3% respectively. Commonest hematological malignancy was acute leukemia (70.73%) followed by chronic myeloid leukemia (6.97%), plasma cell neoplasm (8.13%), myelodysplastic syndrome (4.65%), Non-Hodgkin lymphoma (2.32%) and hypereosinophilic syndrome (1.16%). In cases of acute leukemia 27 presented with bicytopenia, 15 each with pancytopenia and anemia; and seven with thrombocytopenia. Number cases presenting with bicytopenia and pancytopenia in multiple myeloma was one each and with anemia two. Thrombocytopenia was seen in monoclonal gammopathy of undetermined significance. Bicytopenia and pancytopenia were seen in two cases each of myelodysplastic syndrome. Chronic myeloid leukemia and Non-Hodgkin lymphoma showed anemia and pancytopenia respectively. Conclusions: More than 90% of hematological malignancies presented with cytopenia. Bicytopenia and pancytopenia together constituted 58%. 97% of acute leukemia presented with cytopenia and majority of them had pancytopenia or bicytopenia.